Development of a Digital Reseller Platform for Entrepreneurship Learning to Improve Students’ Entrepreneurial Motivation - Stefanus Juan Aristo Secunda; Nurul Fatimah (Jurnal Paedagogy, 2026)
This study aims to develop a learning media based on a Digital Reseller Platform to enhance entrepreneurial motivation among senior high school students. The media is designed to facilitate students’ practical understanding of entrepreneurship concepts through digital simulations while addressing time management challenges in practice-based learning. The study was conducted at SMA Negeri 1 Ungaran, Semarang Regency, using a Research and Development (R&D) method based on the 4-D model, which includes the Define, Design, Develop, and Disseminate stages. The participants included 35 students from one class, a subject teacher, and material and media experts. Data were collected through interviews, observations, and questionnaires to analyze learning needs, evaluate media feasibility, and measure its effectiveness in improving students’ entrepreneurial motivation. The results indicate that the Digital Reseller Platform media is both feasible and effective for entrepreneurship learning. Expert validation demonstrated high feasibility, with scores of 82.5% from media experts and 85.7% from material experts. Furthermore, its implementation resulted in a statistically significant increase in students’ entrepreneurial motivation (F = 4.17, p < .05), as reflected in higher levels of interest, active participation, and confidence in engaging in entrepreneurial activities. In addition, the media supports more efficient time management without compromising students’ understanding of entrepreneurial concepts. In conclusion, the Digital Reseller Platform represents a valid and effective instructional medium for enhancing entrepreneurial motivation in senior high school settings.